21st Century Dissent - Curran, G. author. aut Link
XI, 251 p.
Keywords: 21st Century Dissent contends that anarchism has considerably influenced the modern political landscape. Curran explores the contemporary face of anarchism as expressed via environmental protests and the anti-globalization movement.